Metaverse Technology in Communication Practices: A Case Study of IT Products Retailers in the UAE - Faycal Farhi; Riadh Jeljeli; Khaled Zamoum; Yamine Boudhane; Faten Ben Lagha (Emerging Science Journal, 2023)
Introduction: Retail companies aim to provide their customers with improved customer support and public relations services. For this purpose, metaverse technology is one of the most preferred approaches to improving customers’ buying and post-purchase experiences. Aims: This research also examined metaverse technology acceptance among the IT products and services companies in the United Arab Emirates. Methods: The researchers employed a self-proposed study model and used the structural equation modeling approach. Results: Results revealed that relative advantage significantly affects customer support and public relations. However, transparency does not affect customer service and public relations significantly, while the effect of perceived compatibility on customer support remained insignificant while public relations remained significant. Finally, the effect of public relations on metaverse technological acceptance remained insignificant. Besides, the effect of customer support on metaverse technology acceptance remained significant. Overall, the results supported the role of certain factors proposed by the diffusion of innovation theory in the context of PR and customer support, which is further accelerating the metaverse technology adoption among the IT retailers in the UAE. Conclusion: Thus, this study concludes that the role and adoption of metaverse technology not only highlight its acceptance but also address its importance in improving IT retail products and services. Doi: 10.28991/ESJ-2023-07-03-019 Full Text: PDF